INDUCTION OF INDIRECT SOMATIC EMBRYOGENESIS IN BORNEO IRONWOOD - Gibson, Entuni; Rebicca, Edward (Dr. Leonardo B. Carvalho, 2017)
Induction of indirect somatic embryogenesis in Eusideroxylon zwageri, an endangered and hardest timber tree species in Borneo tropical rainforest, was initiated from immature leaves. Embryogenic callus cultures were induced on Murashige and Skoog medium (MS) containing 3% sucrose, 0.24% Gelrite, and various concentrations and combinations of BAP, NAA and GA3 after 4 weeks of culture in darkness. A higher response (76%) of embryogenic callus was induced on MS medium with 1.0 mg L-1 BAP, 0.5 mg L-1 NAA and 1.0 mg L-1 GA3. Higher numbers of globular- (31), heart- (30), torpedo-(28), and cotyledon-stage (25) embryos per explant were obtained by culturing embryogenic callus on MS with 3% sucrose, 0.24% Gelrite without plant growth regulators after 8 weeks culture in darkness. These results on the induction of indirect somatic embryo in E. zwageri could be used for mass propagation and to select useful traits of this tree species at the cellular level. However, further work needs to be done on the conversion of the regenerated embryos.